A strange thrombus in the left atrial appendage. Issue 9 (September 2018) - Monzo, Luca; Lino, Stefano; Bencivenga, Sabrina; Lanzillo, Chiara; Acitelli, Angelo; Di Roma, Mauro; Calò, Leonardo
Abstract : Supplemental Digital Content is available in the text